Phenotypic Switching in Candida glabrata Involves Phase-Specific Regulation of the Metallothionein Gene MT-II and the Newly Discovered Hemolysin Gene HLP - Lachke, Salil A. (American Society for Microbiology, 2000)
Although Candida glabrata has emerged in recent years as a major fungal pathogen, there have been no reports demonstrating that it undergoes either the bud-hypha transition or high-frequency phenotypic switching, two developmental programs believed to contribute to the pathogenic success of other Candida species. Here it is demonstrated that C. glabrata undergoes reversible, high-frequency phenotypic switching between a white (Wh), light brown (LB), and dark brown (DB) colony phenotype discriminated on an indicator agar containing 1 mM CuSO(4). Switching regulates the transcript level of the MT-II metallothionein gene(s) and a newly discovered gene for a hemolysin-like protein, HLP. The relative MT-II transcript levels in Wh, LB, and DB cells grown in the presence of CuSO(4) are 1:27:81, and the relative transcript levels of HLP are 1:20:35. The relative MT-II and HLP transcript levels in cells grown in the absence of CuSO(4) are 1:20:30 and 1:20:25, respectively. In contrast, switching has little or no effect on the transcript levels of the genes MT-I, AMT-I, TRPI, HIS3, EPAI, and PDHI. Switching of C. glabrata is not associated with microevolutionary changes identified by the DNA fingerprinting probe Cg6 and does not involve tandem amplification of the MT-IIa gene, which has been shown to occur in response to elevated levels of copper. Finally, switching between Wh, LB, and DB occurred in all four clinical isolates examined in this study. As in Candida albicans, switching in C. glabrata may provide colonizing populations with phenotypic plasticity for rapid responses to the changing physiology of the host, antibiotic treatment, and the immune response, through the differential regulation of genes involved in pathogenesis. More importantly, because C. glabrata is haploid, a mutational analysis of switching is now feasible.